Patriarchy and Subordination of Women in Patricia McCormick’s Sold: An Intersectional Approach - Paudyal, Ganga Ram (AWADHARANA, 2025)
This paper explores how female characters are dominated on the basis of gender, age, culture, religion, economic status as well as education in Nepal. This issue is discussed and analyzed on the basis of the textual analysis of Patricia McCarmic’s novel Sold, which is set in the context of Nepal. The novelist expresses multifaceted problems women are facing in rural Nepal in which the decision of the male is final and women have to suffer due to their decision. Many women and girls become the victims of male supremacy every year as they have undergone many tortures and discriminations in their lives. As a qualitative approach of study, it reviews some articles and books concerning McCormick’s novel as a primary source using the intersectional approach through the study of patriarchy and subjugation of women. The finding of this study indicates that the protagonist Lakshmi experiences not only gender discrimination but also marginalization based on class and culture. It also shows that Lakshmi has a strong instinct and determination that enable her to come out of the brothel where she is sold to work as a prostitute. At the end of the novel, she frees herself as well as her friends from that brothel revolting against all kinds of dominations women have faced in the society.